Factors Which Promoted the Interest of the Selected Professionals in Jolo in Obtaining A Master’s Degree - Tandih, Farrah Carlson L. (Open Access Indonesia Journal of Social Sciences, 2021)
This research studied the factors which promoted the interest of the selected professionals in Jolo, Sulu in obtaining a master’s degree. The theory and explanation on interest of Silvia, Kashdan, and Berlyne were used to support the study. The study sought to answer the following questions: 1. What is the profile of the respondents in terms of age, gender, educational attainment, and occupation? 2. What are the factors which promoted the interest of the selected professionals in Jolo in obtaining a master’s degree? 3. What is the level of interest of the professionals in obtaining a master’s degree? 4. Is there significant difference among the factors which promoted the interest of the professionals in obtaining a master’s degree? 5. Is there any significant difference in the interest of the professionals according to their profile? The samples used in this study were the selected professionals in Jolo. They were thirty (30) respondents. The researcher used the following statistical treatment for the hypotheses: Percentage was used in the first question. Weighted mean was employed to treat the second and the third questions. The fourth question used the Friedman Test using the chi-square. The fifth question was analysed with the Kruskal-Wallis Test using chi-square. After the thorough analysis and interpretation of the data, these were the following results: The factors which promoted the interest of the selected professionals in Jolo were prospective rank and promotion, financial condition, aspiring for leadership, staying marketable, community, and a ladder to doctorate. There were ten (10) identified concepts of interest. These were the following: concentration to the lectures, awareness of new-found knowledge, curiosity to further learning, attention to oral reports, readiness in attending classes, willingness to comprehend lectures, eagerness to accomplish researches, enthusiasm to expand skills, keenness to explore broader education, and achievement of wisdom. The level of interest of the selected professionals in Jolo in obtaining a master’s degree in relation to the ten concepts of interest and the factors mentioned was high. In addition to this, their levels of interest in relation to the ten concepts of interest do not differ with each other in terms of their age, civil status, degree obtained, position, length of service, and income. However, in terms of gender, the male and female professionals differ only in their interests as to readiness in attending classes and keenness to broader education.